Non-Digestible Oligosaccharides and Polysaccharides: A Source of Health for Older People [Oligosacáridos y Polisacáridos No Digeribles: Una Fuente de Salud Para Los Adultos Mayores] - Bustos-Cerda, R; Vera-Vera, C; Florez-Mendez, J (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2020)
Since aging naturally leads to an imbalance in the diversity and quantity of microorganisms present in the intestine, older people are particularly vulnerable to diseases associated with the gastrointestinal tract. Thus, supplementing the diet of elderly persons with non-digestible oligosaccharides and polysaccharides (OPND) has gained scientific relevance. Supplementation aims to prevent and (partially) revert the negative changes in intestinal microbiota due to aging. It has been observed that OPND supplementation in older adults provides several benefits, including an improvement in the immune system, increased calcium absorption, a reduction in the incidence of allergies, a reduction in constipation and a decrease in blood levels of cholesterol and glucose. Because the effects of OPND supplementation in older adults has been scarcely discussed in the scientific literature in the Spanish language, the purpose of this review is to address the issue with emphasis on the Chilean and Latin-American reality. The article promotes the incorporation of OPND in processed food and feeding programs specifically designed for older people in Latin America. © 2020, Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All rights reserved.